Awareness of smoking cessation amongst German vascular surgeons: First national survey - Bischoff, Moritz; Meisenbacher, Katrin; Rother, Ulrich; Cotta, Livia; Böhner, Hinrich; Storck, Martin; Behrendt, Christian-Alexander (Vasa, 2024)
Summary: Background: Smoking represents the well-known enemy of vascular well-being. Numerous previous studies emphasised the important role of smoking on the development and progression of atherosclerotic cardiovascular disease. The current study aimed to identify hurdles and barriers for an insufficient implementation of secondary prevention in the treatment of lower extremity peripheral arterial disease (PAD). Methods: All members of the German Society for Vascular Surgery and Vascular Medicine (DGG) with valid email addresses were invited to participate in an electronic survey on smoking. Results are descriptively presented. Results: Amongst 2716 invited participants, 327 (12%) submitted complete responses, thereof 33% women and 80% between 30 and 59 years old (87% board certified specialists). 83% were employed by hospitals (56% teaching hospital, 14% university, 13% non-academic) and 16% by outpatient facilities. 6% are active smokers (63% never) while a mean of five medical education activities on smoking cessation were completed during the past five years of practice. Only 27% of the institutions offered smoking cessation programs and 28% of the respondents were aware of local programs while a mean of 46% of their patients were deemed eligible for participation. 63% of the respondents deemed outpatient physicians primarily responsible for smoking cessation, followed by medical insurance (26%). Conclusions: The current nationwide survey of one scientific medical society involved in the care of patients with vascular disease revealed that smoking cessation, although being commonly accepted as important pillar of comprehensive holistic care, is not sufficiently implemented in everyday clinical practice.